2011
DOI: 10.1002/sim.4130
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imputation analysis of case–cohort studies

Abstract: The usual methods for analyzing case–cohort studies rely on sometimes not fully efficient weighted estimators. Multiple imputation might be a good alternative because it uses all the data available and approximates the maximum partial likelihood estimator. This method is based on the generation of several plausible complete data sets, taking into account uncertainty about missing values. When the imputation model is correctly defined, the multiple imputation estimator is asymptotically unbiased and its varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 19 publications
4
63
0
Order By: Relevance
“…Breslow et al [9] suggested calibrating or estimating the weights a posteriori, using all the phase-1 information, to improve precision with respect to classical weighted estimators. Marti and Chavance [10] showed that multiple imputation (MI) is a good alternative to classical weighted methods for the analysis of case-cohort data. When the imputation model was correct, the MI approach provided unbiased estimators of the log hazard ratios and correctly estimated the variance of its estimators.…”
Section: Introductionmentioning
confidence: 99%
“…Breslow et al [9] suggested calibrating or estimating the weights a posteriori, using all the phase-1 information, to improve precision with respect to classical weighted estimators. Marti and Chavance [10] showed that multiple imputation (MI) is a good alternative to classical weighted methods for the analysis of case-cohort data. When the imputation model was correct, the MI approach provided unbiased estimators of the log hazard ratios and correctly estimated the variance of its estimators.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, concrete proposals for implementation involve assumptions that may limit applicability, for example, to discrete covariates (Nan 2004), to complete independence (not just conditional on covariates) of survival and censoring times (Scheike and Martinussen 2004) and to situations where all the auxiliary variables are included in the model (Zeng and Lin 2014). Multiple imputation of the “missing data” is another option, but requires correct specification of the imputation model for consistency (Marti and Chavance 2011; Keogh and White 2013). Most of these proposals, furthermore, have been restricted to (stratified) versions of the case-cohort design in which all cases (“deaths”) are sampled at Phase II (Prentice 1986; Borgan et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One feasible alternative approach is multiple imputation, though the increased efficiency is gained at the price of assuming a correct imputation model. [21]…”
Section: Discussionmentioning
confidence: 99%